Motion events in Kambaata - (:unkn) unknown (My University, 2007)
Based on oral and written text data, the present article investigates in which morphosyntactic constituents the semantic components of a motion event (i.e. path, manner, figure and ground of motion) are realised in Kambaata. Although the path of motion is lexicalised in many verb roots, the analysis points out the great importance of case morphemes on ground NPs for the encoding of path. Furthermore, the study illustrates how complex motion events are broken up into semantic sub-components and how these sub-components are expressed in separate converbal clauses.
Keywords: African Research